Pengembangan Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode AHP pada Evaluasi Kinerja 360 Degree Feedback - Muhammad Sulthan Rafli Maajid; Silvester Dian Handy Permana; Yaddarabullah Yaddarabullah (LPPM STT Terpadu Nurul Fikri, 2025)
PT. X is a health technology company that provides a cloud-based Management Information System for healthcare facilities. So far, the selection of the best employees has been based solely on supervisors' observations, without a systematic, objective evaluation system. This has led to decreased employee performance and motivation due to the lack of a structured, objective decision-making system. This study aims to develop a performance evaluation system based on the Analytical Hierarchy Process (AHP) method, integrated with the 360 Degree Feedback approach, to provide an objective, structured assessment. The evaluation is conducted based on clear, measurable criteria such as professionalism, performance, attitude, initiative, and teamwork, involving assessments from supervisors, colleagues, subordinates, and self-evaluation, thereby ensuring a more comprehensive assessment and reducing the bias commonly found in single-source evaluations. The results of the study show that the best employees based on this system are Samuel Steven (1.00), Muhammad Sulthan Rafli Maajid (0.947675), and Muhammad Insan Kamil (0.920534). This system is expected to improve evaluation quality and employee motivation by enabling more comprehensive, objective assessments.